Analysis of the Ionic Conduction Behavior in a Few of Room Temperature Molten Fluorides. (20th August 2015) - Tasaka, Akimasa; Inoue, Hidemi; Isogai, Tomohiro; Nakai, Takaaki; Morihiro, Saito; Inaba, Minoru
Abstract: The average self-diffusion coefficients of cations and anions increased with increasing the HF-concentration and temperature in (CH3 )3 N· m HF, (CH3 )4 NF· m HF, (C2 H5 )3 N· m HF, and (C2 H5 )4 NF· m HF melts. The behavior of the self-diffusion coefficients of cations and anions in every melt is in good agreement with an increase in ionic conductivity and a decrease in viscosity. The transference number of (FH) n F − anions estimated from the values of self-diffusion coefficients for each ion in every melt was almost constant and their values were around 0.6 in the (CH3 )3 N· m HF melt and around 0.7 in the (CH3 )4 NF· m HF, the (C2 H5 )3 N· m HF, and the (C2 H5 )4 NF· m HF melts. The value of theoretical conductivity (σNMR ) obtained from the average self-diffusion coefficients of cations and anions by using Nernst-Einstein equation was higher than the value of experimental ionic conductivity (σ). Therefore, it is concluded that the diffusion of (FH) n F − anions is faster than that of each cation in every melt and that a part of both cation and anion in each melt may associate by interaction between both ions.